Communities of interest as a lens to explore the advantage of collaborative behaviour for developing economies: An example of the Welsh organic food sector. (February 2017) - Davies, Paul; Mason-Jones, Rachel
This article introduces the concept of communities of interest (CoIs) as a lens to explore the developing collaborative practice. A shared philosophy between companies offers a means of understanding the behaviour of individuals within a community context. This context is an important element within a developing economy, because this shared experience enables organizations to develop and learn together. The article draws on a study within the Welsh organic food sector to illustrate the way that the CoI concept provides an informative framework to explore interaction. The concept of a shared philosophy providing a distinct community identity is one that can be transposed to a number of sectors and offers a creative lens for developing economies as network connections are seen as integral aspects of how companies are able to grow.